Technical presentation skills - Mandel, Steve (Crisp Pub. Menlo ParkUS, 1994)
Explains how to: plan the content of a presentation; develop and use visual aids; control the presentation environment; conduct question and answer sessions and, deliver a technical paper at a professional meeting.